Identifying Motivation of Parental Involvement and Problems in Homework Encountered By Blind and Low Vision Students - Khu , Li Huang; Karupiah, Premalatha; Nikku, Bala Raju (School of Social Sciences, 2015)
This study aims to understand the motivation of parents to assist their children who are blind or with low vision with their homework and its impact on their academic achievement. Three families have been selected, all of whom have a blind or low vision child who studies at secondary level in a public school. This study employs the in-depth interview to get the views from three pairs of parents. The result leads us to look beyond the relationship between homework management strategies and grades. Therefore, the key outcome of this study leads us to identify the problems in the process of doing homework for blind and low vision students who are taught in public schools. Solutions such as the learning skill in braille, strong parents support group and close engagement among parents and teachers are needed to create the stimulating learning environment to enable blind and low vision students to read, to learn and to write their homework independently. Therefore, the implications of this study are the need to amend the policy to facilitate parental engagement and establish the systematic assessment and planning to ameliorate the barriers faced by blind and low vision students.